European Experience of the Use of Information and Communication Technologies In Initial Education of the English Language Teachers - Komar, Oleh (Educational Challenges, 2020)
The article deals with the analysis of the peculiarities of the use of information and communication technologies in the process of initial education of future English language teachers in the countries of the European Union. The topicality of the problem is based on the current trends in the development of education, in the particular extensive use of online technologies and tools in the process of English language learning and English language teacher education. The purpose of the article is to study the European experience of the use of information and communication technologies in the initial education of the English language teachers and single out the most important and topical of them in order to outline the possibilities of their use in the initial education of teachers of English in a broader context. The methodology of the research is realized with the use of such methods as analysis, synthesis, generalization, analogy and interpretation of empirical data and theoretical concepts; observation and study of practical experience of higher educational institutions in Poland and Portugal as well as an interview with teachers and students of the above-mentioned institutions. As a result, the importance of the development of information and technological competencies in future teachers of English is grounded, the role of information and communication technologies in initial teacher education is determined. Various information and communication technologies used in the educational process, in particular offline technologies and tools as well as online technologies and resources, are presented and analyzed. Attention is also given to the use of E-learning and the implementation of massive open online courses into the initial teacher education of the English language teachers. The conclusion about the variability of information and communication technologies is made.